HUBUNGAN SANITASI DASAR DENGAN KEJADIAN DIARE PADA BALITA DI DESA SANDI KECAMATAN KALEDUPA SELATAN KABUPATEN WAKATOBI - BLACK2017 WAODE AZFARI AZIS (Jurnal Medika Hutama, 2021)
Abstract In 2017 there were 204 cases of diarrhea in Sandi Village, 245 in 2018 and in 2019 from January to July 103 cases. This research aims to knowing relationship clean water supply, trash can and latrines with diarrhea incident at children under five in the village of Sandi, South Kaledupa District. This was a quantitative study with cross sectional study approach. The population in this research were all heads of families who had children under five exactly in Sandi Village, with a total sample of 77 respondents taken using simple random sampling techniques. Measuring instruments used in the form of a questionnaire. Data analysis used univariate and bivariate analysis with using the chi square test. The results obtained that there is relationship between clean water supply, trash can and latrines with diarrhea incident at children under five in the village of Sandi, South Kaledupa District with the chi-square test results obtained values ϸ clean water supply = 0.026 (α <0.05), the value of ϸ trash can = 0.023 (α <0.05), and the value of ϸ latrines = 0.034 (α <0.05). Keywords : clean water suplly, trash can, latrines, diarrhes